Sintesa Surfaktan Metil Ester Sulfonat (MES) Dari Palm Oil Metyhl Ester Dan Natrium Bisulfit Menggunakan Katalis CaO; Variasi Rasio Mol Dan Kecepatan Pengadukan - Hedri Yanti; Syaiful Bahri; Panca Setia Utama (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Surfactant (surface active agent) is a chemical compound used to reduce the surface tension of the liquid. Surfactants are divided into four groups: anionic, nonionic, cationic and amphoteric. The most widely used surfactant is an anionic surfactant which is synthesized from Linier Alkylbenzene Sulphonate (LABS) a petroleum base surfactant. LABS is not ecofriendly, low resistant to high salinity levels, hard to degradable, expensive and still imported. Methyl Ester Sulfonate (MES) is an anionic surfactant which is currently being developed. These surfactants can be produced from POME. MES produced by sulfonation reaction with addition of sulfonation agents. In this research sodium bisulfite used as sulfonation agent. The aims of this research was to synthesized MES from POME and Sodium Bisulfite (NaHSO3) and Calcium Oxide as the catalyst, to characterize the product, and to study the effects of mole ratio and stirring speed of surface tension and emulsion stability MES. POME obtained from PT. Cemerlang Eka Perkasa Dumai Riau Province. Sulfonation process was carry out at the mole ratio of 1:1, 1:1,5 and 1:2, stirring speed of 300, of 500, of 700 rpm, temperature of 80°C, and the time of 6 hours. The best characteristic of the MES was obtain at stirring speed of 500 rpm and mole ratio of 1:2 density of 0,8659 gr/ml; viscosity of 2,002 cP; pH of 3,52; surface tension of 33,3 dyne/cm; interfacial surface tension of 29,2 dyne/cm and emulsion stability of 89%. The yield of 83,51% can be obtained in this research.Keyword : Methyl Ester, Methyl Ester Sulfonate, Sulfonation, Surfactant.